2018
DOI: 10.1088/1361-6560/aaa707
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a high-resolution depth-encoding PET detector module using linearly-graded SiPM arrays

Abstract: The goal of this study was to exploit the excellent spatial resolution characteristics of a position-sensitive silicon photomultiplier (SiPM) and develop a high-resolution depth-of-interaction (DOI) encoding positron emission tomography (PET) detector module. The detector consists of a 30  ×  30 array of 0.445  ×  0.445  ×  20 mm polished LYSO crystals coupled to two 15.5  ×  15.5 mm linearly-graded SiPM (LG-SiPM) arrays at both ends. The flood histograms show that all the crystals in the LYSO array can be res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 30 publications
3
74
1
Order By: Relevance
“…The 500 ps TOF was commonly available in commercial PET scanners (Jakoby et al 2011) and 320 ps TOF has also been reported in recent published work (Peng et al 2015, Miller et al 2015, Zhang et al 2018a). The choice of DOI resolutions also covered the range that had been reported in the literature (Du et al 2018, Zhang et al 2013a, Zhang et al 2013b). Two different activity levels, 20 MBq and 370 MBq, were investigated to represent a low dose and a regular clinical dose studies, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The 500 ps TOF was commonly available in commercial PET scanners (Jakoby et al 2011) and 320 ps TOF has also been reported in recent published work (Peng et al 2015, Miller et al 2015, Zhang et al 2018a). The choice of DOI resolutions also covered the range that had been reported in the literature (Du et al 2018, Zhang et al 2013a, Zhang et al 2013b). Two different activity levels, 20 MBq and 370 MBq, were investigated to represent a low dose and a regular clinical dose studies, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, the readout electronics and position estimation algorithms are more complicated and require very careful calibration compared to PET detectors based on scintillator arrays, which typically use simple center of gravity algorithms to estimate the gamma photon interaction position (Joung et al 2002, Wang et al 2011 and Du et al 2016). Furthermore, the resolution obtained from PET detectors based on thick monolithic scintillators are not in general as good as these obtained from PET detectors based on scintillator arrays (Borghi et al 2018 and Du et al 2018).…”
Section: Introductionmentioning
confidence: 73%
“…The energy resolution and peak position of the 511 keV gamma photons were extracted using the data obtain for the flood histograms. For the DOI measurements, a reference detector consisting of a 0.5 × 20 × 20 mm 3 LYSO crystal and the same PMT was used to electronically collimate the interaction depth (Du et al 2018). The PMT signal was amplified by a transimpedance amplifier (based on AD8045) and then fed in to a CFD (ORTEC 584) for time pick-off.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations